Review of the role of women in the family business, Portoviejo, Ecuador - Lorena mariana Cobacango Villavicencio, Rosario Beatriz Mera Macías, Telly Yarita Macías Zambrano (International Journal of Advanced Science and Technology, 2020)
The research aims to address the role of women in the different functions they perform within family businesses and how this has been made invisible and not yet valued by the results that presents. A mixed approach methodology was used, through intentional sampling, a survey was applied to 200 women linked to family businesses in the city of Portoviejo to determine their role within the microenterprise activity. The results were obtained that the highest percentage of women entrepreneurs are between 20 and 40 years old, an academic training with undergraduate studies, with 5 years of commercial activity mainly, occupying administrative positions, as sister of the owners and daughter. It is concluded that within the economic context of the country, the role of women within family businesses is preponderant, and in some moments the sustainable base for its development. It is interesting to consider a line of research that, together with others from the university, contribute to the visibility of women in the commercial and economic field that moves the productive spheres of the city and the country, contributing to the improvement of the quality of life and the guarantee of good living.